The Concept of Alternative Justice In The Form of Cumulative Criminal Sanctions For Corporate Crimes : Adopting The Concept of Justice of Thomas Aquinas - Eny Maryana (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
: Justice according to Thomas Aquinas is the virtue of justice that involves